Effect of Blended Learning Model on Student Learning Outcomes in Material Structure and Function of Plant Tissues at SMA N 5 Yogyakarta - Wijaya, M.R.T.A.; Winindya, S.; Rakhmiyati (Proceeding International Conference on Religion, Science and Education, 2022)
The COVID-19 pandemic has had a significant impact on various lines of life, including in the world of education. One of the policies made by the government is online learning which is commonly referred to as distance learning (PJJ). The state of the COVID-19 pandemic has begun to be resolved well, so distance learning was later modified into limited face-to-face learning (PTM). This system is carried out by dividing 50% of the students to carry out limited PTM in the classroom while still adhering to health protocols, and the other 50% of students take online learning at their homes. This learning model is called distance learning (PJJ). In practice, this learning will be carried out alternately between students. To increase students’ understanding which is not only from a cognitive perspective, practicum activities are carried out to hone students’ psychomotor skills in making fresh preparations independently with direct observations and portfolio assignments in the form of making practicum reports in order to create a good scientific spirit. This study examines the material on the structure and function of plant tissue with the sample of 4 classes in class XI students of SMA N 5 Yogyakarta. The purpose of this research was to find out how student learning outcomes using blended learning models with practicum activities. The method used in this research is a statistical method. The results of this research indicate that the blended learning model with practical work has a significant effect on student learning outcomes on the material of Plant Tissue Structure and Function.